Estudo sobre a utilização das ferramentas do ambiente Sakai numa instituição de ensino superior - Alves, Paulo (2013)
This study had the goal to analyze the value that higher education students and teachers assign to Schedule, Announcements, Resources, Assignments, Tests, Drop Box, Messages, Forums and Search of Sakai collaborative learning environment and to verify if there is any relation between the value assigned to each tool and the experience that the user has with computers. The data set were obtained from responses to a survey by a sample of students and teachers. The most valued tool for students and teachers for course support were Resources and Announcements. Most students and teachers classify their experience with computers as intermediate. In general, the experience with computers has no influence on the valuation of the Sakai collaborative environment tools.